2017
DOI: 10.1146/annurev-physiol-022516-034110
|View full text |Cite
|
Sign up to set email alerts
|

POMC Neurons: From Birth to Death

Abstract: The hypothalamus is an evolutionarily conserved brain structure that regulates an organism’s basic functions, such as homeostasis and reproduction. Several hypothalamic nuclei and neuronal circuits have been the focus of many studies to understand their role in regulating these basic functions. Within the hypothalamic neuronal populations, the arcuate melanocortin system plays a major role in controlling homeostatic functions. The arcuate pro-opiomelanocortin (POMC) neurons in particular have been shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 176 publications
(270 reference statements)
2
129
0
Order By: Relevance
“…Given the role of POMC neurons in food intake, energy expenditure and glucose metabolism (Toda et al, 2017), we examined whether miR-7 is involved in regulating these processes. To knock down miR-7 expression, the miRNA sponge technology is applied (Pollock et al, 2014).…”
Section: Knockdown Of Mir-7 Results In Obesity In Female Not Male Micmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the role of POMC neurons in food intake, energy expenditure and glucose metabolism (Toda et al, 2017), we examined whether miR-7 is involved in regulating these processes. To knock down miR-7 expression, the miRNA sponge technology is applied (Pollock et al, 2014).…”
Section: Knockdown Of Mir-7 Results In Obesity In Female Not Male Micmentioning
confidence: 99%
“…Hypothalamus is a conserved brain structure that regulates several basic life processes such as feeding, energy expenditure, sleep and wakefulness (Clifford & Bradford, 2015;Dietrich & Horvath, 2013;Saper et al, 2005). The arcuate nucleus (ARC) arises from cells located in the hypothalamic ventricular zone (HVZ) through progressive proliferation, lateral migration and differentiation (Mcclellan et al, 2008;Shimogori et al, 2010;Toda et al, 2017). The ARC consists of two major types of neurons, orexigenic neurons that produce neuropeptide Y (NPY) and agouti-related protein (AgRP) (Joly et al, 2010;Mercer et al, 2011), and anorexigenic neurons that produce proopiomelanocortin (POMC) and cocaine-and amphetamine-related transcript (CART) (Gao & Sun, 2016;Greenman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This homeostatic control is maintained by neurons in various brain regions, among which the hypothalamus is believed to be the key brain area in regulation . The arcuate melanocortin neurons consist of two distinct neuronal populations, which have totally opposite effects on energy intake and expenditure . AgRP and NpY increase food intake and decrease energy expenditure; POMC acts as a break to reduce food intake and induce energy expenditure .…”
Section: Discussionmentioning
confidence: 99%
“…Food intake is regulated by homeostatic controls of appetite that induce hunger (feeding), satiation (suppression of feeding), and satiety (post-meal termination of hunger) 1,2 . Recent studies have identified neurons and neuronal circuits that regulate food intake [3][4][5][6] . For example, the arcuate nucleus of the hypothalamus (ARC) contains various cell types, and receives endocrine and exogenous signals that regulate feeding behaviours.…”
Section: Introductionmentioning
confidence: 99%